Ethnobotany Study Tradition Buang Abu Melayu Sambas as a Biology Learning Resource - Nurdiana Nurdiana; Hanum Mukti Rahayu; Mahwar Qurbaniah (Jurnal Penelitian Pendidikan IPA, 2024)
The district of Sambas has a variety of cultures and traditions. The distinctive characteristic of the district of Sambas is embodied in the uniqueness of the buang abu tradition, which differs from the tradition in other areas. Besides, the tradition involves the use of some local plants. The research is aimed at identifying the types of plants used in the process of buang abu and identifying the suitability and validity of the potential of the plant types in the process of buang abu in Malay Sambas as a source of biological learning. The research uses qualitative descriptive methods. The quality of the potential of plants used in the buang abu tradition as a source of biological learning in the interpretation is very worthy, with a 100% presentation. The relevance of the material to the study of ethnobotany of the tradition of buang abu Melayu Sambas is consistent in achieving basic competence on the material of the high school level, namely biodiversity, classification of living creatures, plantae, growth and development of living beings, and the structure and function of tissues in plants.